Respostas

2014-04-18T16:25:00-03:00
X ( x+1) = 2
x² + x = 2 
x² + x - 2 = 0 
a = 1    b = 1  c = - 2

Fórmula de Bhaskara:
Delta = b² - 4 ac
Delta = 1² - 4 . 1 . ( - 2 ) 
Delta = 1 + 8
Delta = 9 

x' =  - 1 ( b) + 3 ( raiz de 9 )                2 
        ---------------------------            =  ------------      =   1
                     2                                 2

x'' = - 1 - 3        - 4
       ---------- =   -------  = - 2
            2             2 

S = { 2, - 2}


x(x+1)/3-2(x-1)=0
x²+x/ 3x - 2 - 2x + 2  = 0
x² + x / x - 2 = 0
x² +2  = 0

a = 1    b = 0  c = 2


Fórmula de Bhaskara:
Delta = b² - 4ac
Delta = 0 
S= { 0 }